2002
DOI: 10.2460/javma.2002.221.654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term administration of enalapril on clinical indicators of renal function in dogs with compensated mitral regurgitation

Abstract: And Clinical Relevance: Results suggest that administration of enalapril for up to 2 years did not have any demonstrable adverse effects on renal function in dogs with severe, compensated mitral regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 16 publications
4
48
4
Order By: Relevance
“…In contrast, dogs of G2 showed no changes in red blood cell count. Serum levels of biochemical tests showed no significant change absent from deletery effects on liver and kidney functions, thus corroborating with what was described by Haggstron et al (1996) and Atkins et al (2002), studying the use of furosemide and enalapril maleate in dogs with DMMV. Serum sodium and potassium revealed a decline in the animals treated with furosemide, due to increased excretion caused by the medicine (Pereira 1996).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In contrast, dogs of G2 showed no changes in red blood cell count. Serum levels of biochemical tests showed no significant change absent from deletery effects on liver and kidney functions, thus corroborating with what was described by Haggstron et al (1996) and Atkins et al (2002), studying the use of furosemide and enalapril maleate in dogs with DMMV. Serum sodium and potassium revealed a decline in the animals treated with furosemide, due to increased excretion caused by the medicine (Pereira 1996).…”
Section: Discussionsupporting
confidence: 77%
“…In relation to radiography, Soares et al (2004) evaluated the radiographic features of chronic valve disease in dogs with a murmur of low to moderate intensity, describing that only 25% of the evaluated animals had cardiectasia. In relation to echocardiography, Firm & Petric (2002) Atkins et al (2002) have further highlighted its effectiveness after two years of therapy, reporting the absence of laboratory abnormalities in treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma creatinine or urea concentration may progressively increase during ACE inhibitors treatment, most often within the reference range, as previously observed in dogs with CHF treated with quinapril and captopril [26] or benazepril [23]. During long-term ACE inhibitor treatment in similar patients, serum/plasma creatinine remained unchanged with enalapril [70] or tended to decrease with benazepril [58]. GFR also was not altered by benazepril treatment in dogs with decompensating experimental heart failure [15].…”
Section: Specific Adverse Effects Of Ace Inhibitors Reported In Dogssupporting
confidence: 49%
“…Plasma creatinine, ALAT and urea concentrations, and the number of cases of hyperkaliemia were not different between the 2 groups, but more cases of creatinine higher than 124 mol/L occurred in the placebo group. a reference [19], b reference [18], c reference [20], d reference [22], e reference [70], f reference [17], g reference [23], h references [21,58].…”
Section: Enalapril Bmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In an ongoing study of dogs, our laboratory has proven the long-term safety of enalapril in the management of naturally acquired mitral valvular insufficiency. 16 Studies in normal horses by means of enalaprilat IV have shown enalapril to be pharmacologically active, reducing ACE activity and blunting the hypertensive response to angiotensin I. 10,11 Heart failure is a complication of valvular dysplasia, congenital defects, myocarditis, pericarditis, and pulmonary hypertension secondary to heaves in the horse and carries a poor prognosis.…”
Section: Jvim 18_218 Mp_235mentioning
confidence: 99%